Automatic imitation. - Heyes, C (2011)
"Automatic imitation" is a type of stimulus-response compatibility effect in which the topographical features of task-irrelevant action stimuli facilitate similar, and interfere with dissimilar, responses. This article reviews behavioral, neurophysiological, and neuroimaging research on automatic imitation, asking in what sense it is "automatic" and whether it is "imitation." This body of research reveals that automatic imitation is a covert form of imitation, distinct from spatial compatibility. It also indicates that, although automatic imitation is subject to input modulation by attentional processes, and output modulation by inhibitory processes, it is mediated by learned, long-term sensorimotor associations that cannot be altered directly by intentional processes. Automatic imitation provides an important tool for the investigation of the mirror neuron system, motor mimicry, and complex forms of imitation. It is a new behavioral phenomenon, comparable with the Stroop and Simon effects, providing strong evidence that even healthy adult humans are prone, in an unwilled and unreasoned way, to copy the actions of others.